FEMININISATION IN CHINESE DANMEI LITERATURE - Wang, Aiqing (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
耽美 danmei, the Chinese version of Boys Love (BL), literally means ‘addicted to beauty; indulgence in beauty’, and it denotes a literary genre featuring male-male romantic/homoerotic relationships produced for and consumed by 腐女 funü ‘rotten girls’. Although danmei literature and subculture emerged in China’s cyberspace in the 1990s, quasi-danmei depictions can be attested from works composed during the imperial period when male-male homosexuality involving feminine elements was embraced by elite culture. As a controversial, transgressive subcategory of Internet literature, danmei is attaining visibility and critical attention, yet more academic research is needed to comprehensively analyse this relatively new literary genre in a holistic manner. In this paper, I hermeneutically scrutinise a range of danmei fiction and investigate the phenomenon of feminisation prevalent in danmei writings. Currently, a prodigious amount of danmei narratives are characterised by feminisation of uke (bottom) and even seme (top) protagonists, embodied by characters’ epicene appearance, effeminate manners, transvestism and male pregnancy. Feminisation in danmei, however, is discrepant from fangirls’ act of nisu (泥塑/逆苏) that depicts male idols as adolescent girls and youthful women. The rationale for feminisation in danmei is partially attributed to female writers’ (un)intentional deviation from partner preferences of homosexual males, impinged on by the prevailing aesthetic trend of ‘soft masculinity’ and readers’ taste. More significantly, feminising male characters enables danmei creators to manipulate traditional gender roles and intensify the female gaze. Potentially, feminisation is the result of the increasing attention and readership of danmei literature in contemporary China. To cite this article (7th APA style):Wang, A. (2021).  Feminisation in Chinese Danmei Literature. Journal Communication Spectrum: Capturing New Perspectives in Communication 11(2), 127-141.  http://dx.doi.org/10.36782/jcs.v11i2.2022